Adolescents' social media posting, social support, and the moderating role of tech attitudes and self-esteem: a 2-year longitudinal study - Fan, Tingting; Bliss, Lydia; Calvin, Angela; Selkie, Ellen (Frontiers in Psychology, 2025)
IntroductionThis study investigates the reciprocal relationship between adolescents' social media posting behaviors and perceived social support over a 2-year period.MethodsUsing a longitudinal design and observational data on posting frequency, we examined whether posting predict perceived social support from close friends and classmates and whether increased social support, in turn, predicts more frequent posting. We also explored the moderating roles of individual differences in self-esteem and attitudes toward technology.ResultsOur findings revealed a reciprocal relationship within close friend networks. More perceived support from close friends in mid adolescence was linked to more posting in late adolescence, which in turn was associated with more support received from participants' close friend networks in late adolescence. This bidirectional association was not observed within classmate networks. Besides, adolescents from low SES backgrounds and those with lower self-esteem demonstrate significant benefits from social media posting, receiving more social support from close friends, while those with negative attitudes toward technology experienced diminished benefits from posting behaviors in receiving social support.DiscussionThis study sheds insight on the relationship between social networks and social media use by highlighting the ways in which social support relate to adolescents' online behaviors, which further advance our knowledge of how adolescent's preexisting personal traits and posting online interact impact social support that adolescents received.